Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Pegawai Kelurahan Grogol Jakarta Barat : The Influence of Competence and Work Motivation on the Performance of Employees of Grogol Village, West Jakarta - Seta Aqilah; Frida Aprillia (CV Warnak Johanna Nusantara, 2026)
The evolving world of work increasingly demands organizations to have quality human resources to achieve optimal performance. Competence and work motivation are two important factors that play a role in improving employee performance. This study aims to identify the relationship between competence and work motivation and employee performance in the institution. A quantitative method using a questionnaire was used as the data collection instrument. The research sample consisted of 40 employees. The data obtained were analyzed using multiple linear regression analysis, validity tests, reliability tests, classical assumption tests, partial tests, simultaneous tests, and coefficient of determination tests using SPSS version 27. The results of this study state that Competence with a calculated t value of 0.227 < t table 2.026 and a significance value of 0.822 > 0.05 partially competency does not significantly influence employee performance, while Work Motivation with a calculated t value of 3.340 > t table 2.026 and a significance value of 0.002 < 0.05 partially work motivation significantly influences employee performance. Competence and Work Motivation with a calculated F value of 14.136 > F table 3.25 with a Sig. value of 0.000 < 0.05 simultaneously have a significant influence on employee performance.